HUBUNGAN ANTARA GRATITUDE DAN PEER SOCIAL SUPPORT TERHADAP PSYCHOLOGICAL WELL-BEING PADA SISWA SMA - Saniyya Dewi Nur Hafizhah; Muslikah (IKIP Siliwangi, 2026)
This study focuses on the relationship between gratitude and peer social support and psychological well-being among high school students. The research instruments included a 24-item gratitude scale (McCullough et al., 2002) with validity and reliability of 0.873, a 24-item peer social support scale (Sarafino & Smith, 2011) with validity and reliability of 0.921, and a 42-item psychological well-being scale (Ryff, 1989), which is an adapted instrument with reliability proven to be adequate based on previous studies. The study was conducted at SMA Muhammadiyah 1 Blora, SMA Muhammadiyah 5 Todanan, and SMA Muhammadiyah Cepu. A quantitative correlational approach was employed, with data collected through interviews, questionnaires, and psychological scales using a Likert scale. The population consisted of 509 students, with a sample of 224 Muhammadiyah senior high school students in Blora Regency selected using the Slovin formula through proportionate stratified random sampling. Data were analyzed using descriptive analysis and multiple linear regression techniques. The results of the multiple linear regression analysis indicated a relationship of 41.7% between gratitude and peer social support and students’ psychological well-being, while the remaining variance was influenced by factors not examined in this study. The researcher recommends that school counselors develop individual, group, and classroom guidance services focusing on strengthening gratitude and peer social support to enhance students’ psychological well-being.